PERENCANAAN WIRE ROPE UNTUK TIANG AGUNG DENGAN KAPASITAS 1 TON KAPAL DHARMA RUCITRA VIII - Rizal Indrawan; Mohamad Hakam; Ahmad Mulya Farizki, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Wire rope is one of the most important elements in bracing and moving loads that can withstand tensile forces when holding up tall poles. In this case what needs to be considered is stress and strain, and predicting the life of the wire rope. This study aims to obtain a wire rope planning that is suitable for a capacity of 1 ton. The types of wire rope used in this study are 6x19+1 with a diameter of 12 mm and 6x37+1 with a diameter of 9 mm. The maximum stress produced on wire rope type 6x19+1 is 11.02 kg/mm2, and type 6x37+1 is 18.1 kg/mm2, where the material allowable stress is 36 kg/mm2. The strain on wire rope type 6x19+1 is 23.63 mm and type 6x37+1 is 38.81 mm. The life of wire rope type 6x19+1 is 34.6 months and type 6x37+1 is 17.3 months. The results of this study show that wire rope types 6x19+1 and 6x37+1 are safe to use against the load of the grand pillar. The recommended wire rope is type 6x19+1 with a diameter of mm because it is considered safe to withstand the structure, and has a service life that is in accordance with the ship's maintenance schedule